Immunoglobulin induced hyponatremia in Guillain-Barré syndrome: A rare occurrence (Indian Journal of Case Reports, 2020)
Guillain-Barré syndrome (GBS) is an acquired, inflammatory peripheral neuropathy characterized by progressive ascending, symmetrical muscle weakness, and depressed or absent deep tendon reflexes. Here, we report the case of a 55-year-old male who presented to the emergency with a history of sudden onset weakness of bilateral lower and upper limbs, in ascending order for 3 days. He was diagnosed with GBS and appropriate treatment with intravenous immunoglobulin (IVIG) was started. The course of the treatment was assessed meticulously. Undesirable effects from IVIG are reported to occur in up to 5–15% of all IV infusions. Most of these are mild, reversible, and transient. Various studies have proven pseudohyponatremia to be a known complication of IVIG. In this case report, we demonstrate that IVIG administration can result in true hyponatremia and it can be deleterious if meticulous care and concern are not provided to the patient.